Asymmetry of lineages and the direction of evolutionary time - Gould, Stephen Jay; Gilinsky, Norman L.; German, Rebecca Z. (1987)
Evolutionary time has a characteristic direction as demonstrated by the asymmetry of clade diversity diagrams in large statistical samples. Evolutionary groups generally concentrate diversity during their early histories, producing a preponderance of bottom-heavy clades among those that arise early in the history of a larger group. This pattern holds across taxonomic levels and across differences in anatomy and ecology (marine invertebrates, terrestrial mammals). The quantitative study of directionality in life's history (replacing vague, untestable, and culturally laden notions of ``progress'') should receive more attention from paleobiologists.